Pemanfaatan Limbah Kardus untuk Pembuatan Headpiece sebagai Peluang Berwirausaha - Albeta Qoiru Ummah; Agus Susanti; Sofia Daniati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The benefit of cardboard waste as a headpiece is to encourage the entrepreneurial spirit to continue to be creative in processing this inorganic waste into products at prices that are relatively cheap compared to prices on the market. Data collection uses the methods of Observation, Literature, Experimentation, Documentation, Interviews, Questionnaires. The author carried out the process of using cardboard waste to make headpieces through several stages, not only that, the author also carried out experiments 3 times using different dyes. In experiment 1 using gold pilok, experiment 2 used gold pilok then sprinkled with gold glitter, then experiment 3 used wall paint coloring sprinkled with gold glitter. The author conducted a sensory test regarding the public's acceptance of headpiece products made from cardboard waste. The highest average results were obtained in experiment 3 with a total average color of 2.87 which means quite appropriate, a total average texture of 2.63 which means quite suitable, a total average design of 1.77 which is less appropriate, while the total average ease of use is 2.67, which means it is quite appropriate. So the results obtained were that as many as 30 respondents preferred product 3 with quite appropriate criteria. From the results of the products made, the coloring still needs to be improved so that they are more perfect and the designs are developed to be more varied so that they can be used as a reference for further research.